2022
DOI: 10.1039/d2ce00670g
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen and halogen bond synergy in the self-assembly of 3,5-dihalo-tyrosines: structural and theoretical insights

Abstract: Halogenation, generally introduced on aromatic aminoacids, is becoming a key supramolecular tool in peptides. Herein, we report the crystal structures and DFT study of two bis-halogenated tyrosines showing the subtle...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…11 Some of us reported that halogenation can be exploited as an effective single-point modification 12 to amplify the selfassembly properties of some peptide sequences 13 derived from amyloid beta (Aβ) 14 and human calcitonin (hCT), 15 whose fibrillation may be related to the occurrence of AD and medullary thyroid carcinoma, respectively. Very recently, bromination of tyrosine residues 16 was proved as an efficient strategy to promote the self-assembly and the consequent emergence of elastomeric properties in a short peptide derived from resilin. 17 In this view, with the purpose of expanding the available tools to strengthen peptide fibrillation, possibly alternative to halogenation, and considering the growing need for new tailored fibril-forming peptides, herein we report a computational approach, based on coarse-grained molecular dynamics (CG-MD), [18][19][20][21][22][23] enabling the identification of new promising peptide sequences at a relatively low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Some of us reported that halogenation can be exploited as an effective single-point modification 12 to amplify the selfassembly properties of some peptide sequences 13 derived from amyloid beta (Aβ) 14 and human calcitonin (hCT), 15 whose fibrillation may be related to the occurrence of AD and medullary thyroid carcinoma, respectively. Very recently, bromination of tyrosine residues 16 was proved as an efficient strategy to promote the self-assembly and the consequent emergence of elastomeric properties in a short peptide derived from resilin. 17 In this view, with the purpose of expanding the available tools to strengthen peptide fibrillation, possibly alternative to halogenation, and considering the growing need for new tailored fibril-forming peptides, herein we report a computational approach, based on coarse-grained molecular dynamics (CG-MD), [18][19][20][21][22][23] enabling the identification of new promising peptide sequences at a relatively low cost.…”
Section: Introductionmentioning
confidence: 99%
“…Some of us reported that halogenation can be exploited as an effective single-point modification 12 to amplify the self-assembly properties of some peptide sequences 13 derived from amyloid beta (Aβ) 14 and human calcitonin (hCT), 15 whose fibrillation may be related to the occurrence of AD and medullary thyroid carcinoma, respectively. Very recently, bromination of tyrosine residues 16 was proved as an efficient strategy to promote the self-assembly and the consequent emergence of elastomeric properties in a short peptide derived from resilin. 17 …”
Section: Introductionmentioning
confidence: 99%